Rzeźby Madonny z Dzieciątkiem w tradycji łacińskiej Europy między IX a początkiem XIII wieku. Antropologia piękna według św. Bernarda z Clairvaux .......... 229 - Mazurczak, Urszula Małgorzata (Dzieje i kultura Cystersów w Polsce, 2025)
THE SCULPTURES OF THE MADONNA AND CHILD IN THE LATIN EUROPEAN TRADITION BETWEEN 9TH AND THE BEGINNING OF 12TH CENTURY. THE ANTHROPOLOGY OF BEAUTY ACCORDING TO ST BERNARD FROM CLAIRVAUX (PART I)The meaning of St Bernard and the Cistercian Order for the Church, through faith and culture, is widely discussed in this extensive bibliography. This text is devoted to the theme of the sculptures of the Madonna and Child which are widespread as freestanding statues in Latin church apses. The statues had been sculpted before the establishment and development of the Cistercian Order between the 9th-12th centuries. They were made popular in Europe and in Poland through Cistercian theological anthropology in the 12th-13th centuries. The stylistic diversity of the figures reflects the rich language of metaphors, allegories and metonymy in the Cistercian Mariology. Furthermore, the text indicates the regionalism of these sculptures which have often been referred to as primitive, because they are thought to have been created by itinerant wood carvers when, in fact, they are the outcome of Cistercian songs and prayers. Among these there are also the sculptures of elite status which refer to ancient tradition. The Cistercian circles knew the patristic texts of pre-scholastic philosophy and of Roman literature. The Cistercian writings developed the vocabulary which reflects the feelings, empathy and spiritual emotional engagement in honor of the Virgin Mary and Jesus. The statues of Mary created in the 12th and in the first part of the 13th century occur as three types: 1) classicizing in proportions but simplified in reflecting the corporeality, with only the simplified arrangement of the draperies of the garments; 2) varied in body proportions, with a big head and enlarged hands; 3) exposing the emotional nature of Mary and Jesus through presenting their smiles, touch, gestures, kisses. In the Latin tradition, coats were put on the Marian sculptures, indicating the liturgical meaning of their garments and reflecting the votive attires of the Greek icons.